AI results complementing the 2020 Annual Report on surveillance for Avian Influenza in poultry and wild birds in Member States of the European Union - Iceland - Icelandic Food and Veterinary Authority (Zenodo, 2021)
This dataset containsthe results of the EU co-funded surveillance activities conducted in 2020, which consisted of: Serological surveys to monitor the circulation of AIV subtypes H5 and H7 in poultry (active surveillance). These surveys should preferentially target poultry species or production systems with increased risk for introduction of avian influenza (AI). Passive surveillance aiming at the virological detection of AI in wild birds found dead or moribund. IS; CSV; zoonoses_support@efsa.europa.eu